Justice-involved males’ procedural justice perceptions of the police and courts: examining the spill-over effect - Alward, Lucas M. (Criminal justice studies, 2021)
Prior research has demonstrated the importance of the process-based model for effective police-citizen encounters and court procedures. Despite considerable research into procedural justice, there is a dearth of research examining high-risk populations. In particular, with few exceptions, research examining perceptions of procedural justice among serious justice-involved males has been nearly absent from the literature. In addition, few studies have explored the interrelationship of individuals’ procedural justice perceptions of the police and courts. Using data collected from a sample of incarcerated males this study explores the relationship between justice-involved males’ procedural justice perceptions of the police and their procedural justice perceptions of the courts. Implications and directions for future research are discussed.